Decentralizing genetic testing for biodiversity monitoring and biosurveillance with the Nucleic Acid Barcode Identification Tool (NABIT) - Holmes, Hal R.; Winters, Misa; Fang, Cifeng; Fotouhi, Gareth; Baron, Maria Fernanda; Day, David L.; Mercader, Jacqueline; Fox, David Anthony; Bunje, Paul M.E.; Dehgan, Alex (Frontiers in Conservation Science, 2025)
The escalating threats to biodiversity, public health, and food security posed by emerging infectious diseases, wildlife trafficking, and invasive species expansions require novel approaches to biosurveillance. Modern genetic testing technology can detect many of these unseen threats, but existing genetic testing approaches are largely inaccessible to most people working in the field. The Nucleic Acid Barcode Identification Tool (NABIT) is a handheld, battery-powered device that enables rapid nucleic acid amplification tests to be performed at the point-of-contact by non-technical users, creating a critical bridge between centralized laboratories and the field by reducing barriers to accessible and routine genetic testing. In this work, we present initial performance data for the NABIT and lyophilized assays for nucleic acid amplification testing of two diverse applications to demonstrate the potential of the NABIT to serve as a platform for on-site biosurveillance and species detection. The results demonstrated that the NABIT COVID-19 test kit could detect SARS-CoV-2 at 0.93 NDU/µL. The NABIT sockeye test kit showed amplification between 13–22 minutes from filtered water samples from a salmon hatchery.